유역-호소 통합수질예측 기법을 이용한 오염원 입지규제에 의한 팔당호 수질개선효과 평가 - 오희상(Heesang Oh); 이한필(Han-Pil Rhee); 조성진(Seong Jin Cho); 이상우(Sang-Woo Lee); 황하선(Ha Sun Hwang) (Daehan hwan'gyeong gonghag hoeji, 2023)
「한강수계법」 제정 이후, 현재까지 추진된 한강수계 수질보전을 위한 다양한 환경정책 및 수질개선 사업에 대해, 직·간접적 기여도와 효과의 종합적 분석은 부족한 실정이다. 그 중, 오염원 입지규제에 의한 효과는 규제되지 않은 조건에서의 현재 상황이 존재하지 않으므로, 미규제 상황을 유추하고 모델 예측을 통해 추정해야 한다. 본 연구에서는 한강수계 상수원관리지역 중 팔당댐 상류 지역의 입지 규제지역이 위치한 강원, 경기, 충북의 평균 오염원 밀도와 입지 규제지역의 오염원 밀도를 비교 분석함으로써, 입지규제 및 행위제한이 없었을 경우 미규제 지역 수준의 오염원이 입지하였을 것으로 가정하여 규제지역의 오염원 변화를 추정하였다. 한강권역은 댐호소가 다수 존재하여 유역모델만으로 호소의 수질을 모의하는데 어려움이 있어 BASINS/WinHSPF와 EFDC-WASP을 연계 구축하였다. 구축 및 보정된 모델에 오염원 입지규제가 시행되지 않았을 경우의 배출부하량을 적용하여 팔당호 수질개선을 평가하였다. 오염원 입지규제의 효과로 입지 규제지역의 배출부하량은 BOD 53.90%, T-P 48.58% 저감된 것으로 나타났으며, 팔당댐 수질은 BOD는 6.77%, T-P는 6.62% 개선된 것으로 나타나 오염원 입지규제가 팔당호 수질개선에 일정부분 기여한 것으로 분석되었다. 팔당호 수질개선 효과는 상류 전체의 영향까지 누적되므로 규제지역 내 오염부하량 저감효과에 비해 상대적으로 낮게 평가된 것으로 판단된다. 오염원 입지규제는 한강수계 전체면적 대비 상대적으로 면적이 매우 협소한 팔당호 인근의 입지규제에도 불구하고 일정수준 이상 수질개선에 효과를 가지는 것으로 분석되었다. Since the enactment of the 「Han-River Watershed Act」, comprehensive analysis about direct and indirect contributions and effects of various environmental policies and water quality improvement projects for the preservation of water quality in the Han-River watershed is insufficient. Especially, effect of pollutant source location regulation should be inferred and estimated through model prediction cause it does not exist unregulated conditions. In this study, average pollutant density of Gangwon-do, Gyeonggi-do, and Chungcheongbuk-do, where the regulation areas located and average pollutant density of water source management areas were compared and analyzed. After that changes in pollutant sources in regulation areas were estimated by assuming load of pollutant sources in unregulated areas that load of pollutant sources in regulation areas. Since many reservoirs are located in Han-river watershed, it is difficult to simulate the water quality of Paldang reservoir using only watershed model, BASINS/WinHSPF and EFDC-WASP were linked. Water quality improvement of Paldang reservoir was evaluated by applying the discharge load when the pollution source location regulation was not implemented to the calibrated model. As a result of the pollution source location regulation, discharge load in the location regulation area was analyzed to reduced by 53.90% and T-P by 48.58%, and the BOD and T-P improvement effect of Paldang Dam was analyzed 6.77% and T-P 6.62%. Since the water quality improvement effect of Paldang Lake is accumulated to the entire upstream, it is evaluated relatively less than pollutant load reducing effect. It was analyzed that pollutiont source location regulation has water quality improvement effect, despite the small area which only located in near Paldang reservoir compared to the total area of the Han-River watershed. KCI Citation Count: 0